Respon Siswa terhadap Penggunaan Modul Elektronik Berbasis Mastery Learning dalam Pembelajaran Matematika - Yulianti, Desy; Marhaeni, Nafida Hetty (Innovative: Journal Of Social Science Research, 2025)
The purpose of this study was to determine how students respond to the use of mastery-based electronic mathematics learning modules. This quantitative descriptive study examines the level of student satisfaction when learning mathematics with mastery-based electronic modules. The data to be used comes from student response questionnaires. This study involved 36 students from SMA Negeri 1 Seyegan who were in class X.E4. The data collection method used a questionnaire containing statement items. These statements cover four assessment components: suitability to the mastery learning approach, interest, material and presentation, and use of language. The results showed that student responses in large-scale tests were categorized as "Very Good" with an average of 71.97, and in small-scale tests were categorized as "Good" with an average of 69.55. Therefore, it can be concluded that mastery-based electronic learning modules have a positive response from students as a learning medium. This module can also be used practically to teach mathematics.